The Pengembangan Minuman Segar Es Buah Nipah di Nagari Seulayat Ulakan Padang Pariaman - Almi, Ara Annisa (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
Business planning is an important thing for nipah fruit fresh drinks business actors in nagari Seulayat Ulakan to work together with the community in terms of meeting community needs, managing village assets, managing independently and increasing the economic potential of nagari Seulayat Ulakan. The problem identification of nipah fruit fresh drinks business actors in nagari Seulayat Ulakan is that they do not have a business development plan, have not determined the form of business to be run, and how marketing with the implementation of digitalization. The solution offered in this activity is to determine the business development plan and the form of business to be carried out, and formulate the right form of digitalization to use. The form of community service activities is carried out based on the lecture method, FGD method, discussion method and business consultation method. The output of this activity is the formation of cooperation between business actors and KKN students, identification of problems, and determining the description of business development planning for nipah fruit fresh drinks in nagari Seulayat Ulakan.